Navigating intensive altered states of consciousness: How can the set and setting key parameters promote the science of human birth? - Dahan, Orli (Frontiers in Psychiatry, 2023)
The subjective childbirth experience is crucial from a public health standpoint. There is a correlation between a negative childbirth experience and a poor mental state after birth, with effects that go far beyond the postpartum period. This paper offers a new approach as to how birthing experiences, and birth in general, can be navigated. The theory of set and setting proves that psychedelic experiences are shaped, first and foremost, by the mindset of an individual entering a psychedelic experience (set) and by the environment in which the experience takes place (setting). In research on altered states of consciousness during psychedelic experiences, this theory explains how the same substance can lead to a positive and life-changing experience or to a traumatic and frightening experience. Because recent studies suggest that birthing women enter an altered state of consciousness during physiological birth (“birthing consciousness"), I suggest analyzing the typical modern birthing experience in terms of set and setting theory. I argue that the set and setting key parameters can help design, navigate, and explain many psychological and physiological elements of the human birth process. Thus, an operative conclusion that emerges from the theoretical analysis presented in this paper is that framing and characterizing the birth environment and birth preparations in terms of set and setting is a central tool that could be used to promote physiological births as well as subjective positive birthing experiences, which is currently a primary, yet unreached goal, in modern obstetrics and public health.